The effect of COVID-19 school closures on adolescent sleep duration: an uncontrolled before-after study - Qiguo Lian; Xiayun Zuo; Xiangyang Zhong; Xiaowen Tu; Jiashuai Zhang; Chang Shu; Chunyan Yu; Chaohua Lou (BMC, 2021)
Abstract Background The coronavirus disease 2019 (COVID-19) pandemic affected almost 1.6 billion students or more than 90% of learners globally. However, the effect of school closures during COVID-19 pandemic on adolescent sleep duration remains unclear. Methods We undertook a cross-sectional electronic survey in six junior and senior high schools in Shanghai, China from late June to early July 2020. We evaluated the changes of sleep duration on weekdays by comparing sleep duration hours and insufficient sleep (< 9 h for children aged 6-13 years or < 8 h for teenagers aged 14-17 years) in COVID-19 school closures and after school reopening. We also investigated possible sex differences in the changes of sleep duration. Results A total of 3265 students completed the survey, the mean age was 14.56 ± 1.99 years, 1567 (47.99%) were girls and 1344 (41.17%) were in grades 10-12. The overall sleep duration decreased from 8.88 h in school closures to 7.77 h after school reopening, and the change (difference: − 1.11 h; 95%CI: − 1.16, − 1.07; P < 0.001) was statistically significant. The prevalence of insufficient sleep increased sharply from 21.10 to 63.98%, and the change (ratio:3.03; 95%CI:2.84, 3.23; P < 0.001) was statistically significant. Besides, the changes were greater in girls than in boys. Conclusion Results of this study revealed that sleep duration was longer and percentage of sufficient sleep was higher during COVID-19 school closures in adolescent students.